Unravelling the key factors of e-government systems effectiveness: a user behavior perspective - Dewi, Bitaria Citra; Sentosa, Ilham; Yafi, Eiad; Muhasyah, Surano (Indonesia Research and Study Center, 2025)
As digital governance becomes integral to modern public service delivery, evaluating the effectiveness of e-government systems through the lens of user behavior is increasingly essential. This study explores the critical success factors influencing the effectiveness of e-government services provided by the Indonesian Ministry of Foreign Affairs, using the DeLone and McLean Information System Success Model as the theoretical foundation. The model’s core dimensions : system quality, information quality, service quality, use, user satisfaction, and individual performance, are examined to understand how these interrelated constructs shape user experience and performance outcomes. Employing a quantitative approach, data were collected from 384 valid respondents through structured questionnaires. Structural Equation Modeling (SEM) using AMOS was applied for data analysis. The results confirm that system quality, information quality, and service quality significantly influence both user satisfaction and usage intensity, which in turn have a positive impact on individual performance. The findings provide empirical validation of the DeLone and McLean model in the e-government context and offer practical insights for enhancing the design and delivery of digital public services based on user-centric performance indicators.